Penerapan Media Flashcard untuk Meningkatkan Kemampuan Menghafal Kosa Kata Bahasa Arab Siswa Kelas VII SMP YAPIDA Gunung Putri Bogor - Agustin, Nia Amelya; Lisnawati, Santi; Triwoelandari, Retno (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background of the problem in this research is that class VII students of SMP Yapida have difficulty mastering or memorizing Arabic vocabulary. This study aims to determine whether there is an increase in memorizing Arabic vocabulary for class VII students of SMP Yapida by applying flashcard media. The research method used is Classroom Action Research (CAR), the model used is the Stephen Kemmis and Robin Mc. Taggart. This research includes 2 cycles, each cycle through 4 stages, namely: planning, implementing, observing and reflecting. Data collection used in the form of observation, interviews, tests and documentation. The results showed that there was a significant increase in the ability to memorize students' Arabic vocabulary in class VII B. This was evidenced by the learning outcomes of students who completed cycle I reached 57% and cycle II reached 81% of 21 students. The results of the interviews conducted concluded that students were very enthusiastic in participating in learning Arabic using flashcard media. Students more easily understand Arabic vocabulary (mufrodat) and the learning atmosphere becomes fun and not boring. This study concluded that memorizing Arabic vocabulary using flashcard media can improve students' Arabic vocabulary memorization (mufrodat).